Studi Literatur Pengaruh Pembelajaran Strategi Konflik Kognitif Terhadap Kompetensi Mahasisa dalam Mata Kuliah Algoritma dan Pemrograman Komputer - Luthviah Aprilliza Utami; Yahfizham Yahfizham (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
As information technology advances, so do the competencies or skills that students need in the twenty-first century to meet the demands of the industrial era 4.0. Students' poor ability to analyze and construct algorithms for computer programming is a difficulty when it comes to learning algorithms and computer programming. In courses on algorithms and computer programming, students' proficiency is impacted by their lack of analytical abilities. It is believed that generative learning based on cognitive conflict methods can improve students' proficiency in computer programming and algorithm creation. Because of this, studies have been conducted to gather information from a variety of sources about the impact of learning cognitive conflict management techniques on students' proficiency in computer programming and algorithms courses. by use the Systematic Literature Review approach to examine the literature. The books and several earlier publications whose titles are so that students can increase the quality of the combination of knowledge regarding learning methods for cognitive conflict strategies on student competency are the sources for this collection of articles. It is envisaged that the use of programming algorithms will facilitate the easy advancement of technological knowledge.